Guru Danau's Religious Study, A Study of Scholarly Identity and Religious Citizenship Practices in Pandamaan Village - Amanda Febria Tilah; Rabiatul Adawiah (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to describe the scientific identity of Guru Danau as a religious figure recognized by the Pandamaan Village community. A qualitative approach is used to closely understand Guru Danau’s exemplary role and his religious studies as a means of developing the religious character of adolescents in Pandamaan Village. Data collection began with direct observation of adolescent religious citizenship practices, continued with interviews with several community members to enrich perspectives, and documented the research atmosphere. Research subjects were selected purposively, namely those directly involved in the research events. The researcher sorted important data before further analysis, then presented the data systematically, and then drew conclusions based on the data that answered the problem formulation. It was found that Guru Danau’s identity was constructed by his religious approach with the community, which gave his teachings moral and social legitimacy for the community. The Guru Danau study group is considered a potential vehicle for fostering religious citizenship among adolescents, with its practice manifesting not only in attending the group but also in transforming adolescents into individuals with social awareness and responsibility within the community.